Modelling Changes in Soil Phosphorus When Phosphorus Fertiliser Is Reduced or Ceases - Tyson, Jessica; Corkrey, Ross; Burkitt, Lucy; Dougherty, Warwick (Frontiers in Environmental Science, 2020)
In order for land managers and policy makers to manage excessive soil phosphorus (P) concentrations and reduce the risk of this particular source of P from impacting water bodies, models of soil P decline under various scenarios are needed. We modelled the decrease in calcium chloride-extractable P (CaCl2-P), and sodium bicarbonate-extractable P (Olsen-P and Colwell-P) using data from six Australian grazed pasture soils with contrasting P sorption properties, over a period of 4.5 years. Each soil had four initial soil P concentrations (Pinit), each of which received four on-going rates of P fertiliser (Pfert). The model predicts the final P concentration (Pfinal) by taking into account the P concentration previously measured (CaCl2-P, Olsen-P or Colwell-P), Pfert applied since measurement, and time since previous measurement: Final P concentration = (previously measured P concentration + ep x P fertiliser applied) exp (-dp x years since previous P concentration measurement). Where ep is the increase in soil P for each unit of applied P and dp is the decay constant representing how quickly the soil P decreased. The greatest decreases in proportion to Pinit occurred for CaCl2-P, followed by Olsen-P, and then Colwell-P. The model tended to fit the dataset well for Olsen-P and Colwell-P, with mean overestimation (modelled Pfinal concentration greater than actual Pfinal) of the Pfinal concentrations of 6.1 (32%) and 4.3 mg/kg (10%), respectively. Although there was less CaCl2-P data, the model successfully described it, with a mean overestimation of Pfinal CaCl2 of 3.1 mg/kg (26%). The overestimation of Pfinal CaCl2 was possibly due to the high CaCl2-P concentrations of the low P buffering index soils. The model predicted an average of 32 years (ranging from 26 to 49 years) for Olsen-P concentrations of between 55 and 96 mg/kg to decrease to an agronomic optimum of 17 mg/kg. Agronomic optimum was not a reliable indicator of environmental risk as some soils did not exceed the CaCl2-P environmental threshold until Olsen-P concentrations were twice the agronomic optimum, whereas low P sorbing soils tended to exceed the threshold before reaching agronomic optimum. Further work with more soils is required to examine the influence of soil properties – such as P sorption – on decreases in soil P.